Phytochemical Constituent and Cytotoxic Activity of Eusideroxylon zwageri Teijsm & Binn Extract and Sub-Fraction on Human Breast Cancer Cell Line T47D - Yayan Rabbani Kurniawan; Adlis Santoni; Suryati Suryati (Molekul, 2023)
Eusideroxylon zwageri Teijsm. & Binn T has been reported to have bioactivity, one of which is the potential as an excellent cytotoxic agent using the BSLT method. So far, stage tests using cancer cells and analysis of the content of secondary metabolites have not been reported, Therefore, it is essential to analyze the content of secondary metabolites using Liquid Chromatography – Tandem Mass Spectrometry (LC-MS/MS) and determination of cytotoxic activity using Brine Shrimp Lethality Test (BLST) mwthod with various solvent polarities. Then separation by bioassay-guided isolation using column chromatography of the active extract assay BSLT. Furthermore, the cytotoxic activity of the active extract and the active isolate was tested against T47D cancer cells with Microculture Tetrazolium (MTT) method. The results of the analysis of the content of secondary metabolites using LC-MS/MS identified senbusine B and 6,7-Dehydroartemisinic acid on hexane extract, while the ethyl acetate extract produced 4 compounds, and 15 compounds were identified in the methanol extract. The results of the cytotoxic activity test using the BSLT method on each extract showed that the hexane extract was the most active, with an LC50 of 17.56 mg/L. Furthermore, the cytotoxic activity of hexane extract against T47D cells showed weak activity with an IC50 value of 237.5 mg/L, while the AB1 sub-fraction showed moderate activity with an IC50 value of 138.4 mg/L. The results of the analysis using HPLC indicated that the active isolate in the form of sub-fraction AB1 contained the compound senbusine B.